2017
DOI: 10.1038/nature24460
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative microbiome profiling links gut community variation to microbial load

Abstract: Current sequencing-based analyses of faecal microbiota quantify microbial taxa and metabolic pathways as fractions of the sample sequence library generated by each analysis. Although these relative approaches permit detection of disease-associated microbiome variation, they are limited in their ability to reveal the interplay between microbiota and host health. Comparative analyses of relative microbiome data cannot provide information about the extent or directionality of changes in taxa abundance or metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
855
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 851 publications
(971 citation statements)
references
References 41 publications
47
855
9
2
Order By: Relevance
“…We herein showed the presence of the same four enterotypes described recently25 explaining 40% of the variation in microbiome composition (R 2 =0.4; permutational multivariate analysis of variance (PERMANOVA) tests) (online supplementary figure 1), yet there was no significant association of enterotype composition and BSS at baseline (Fisher’s test p=0.97 (AGB) and p=0.57 (RYGB)). Interestingly, we observed that patients with the B2 enterotype were those with the lower MGR, whereas those with the Ruminococcaceae enterotype (although few in numbers) were indeed those with the higher MGR.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…We herein showed the presence of the same four enterotypes described recently25 explaining 40% of the variation in microbiome composition (R 2 =0.4; permutational multivariate analysis of variance (PERMANOVA) tests) (online supplementary figure 1), yet there was no significant association of enterotype composition and BSS at baseline (Fisher’s test p=0.97 (AGB) and p=0.57 (RYGB)). Interestingly, we observed that patients with the B2 enterotype were those with the lower MGR, whereas those with the Ruminococcaceae enterotype (although few in numbers) were indeed those with the higher MGR.…”
Section: Resultssupporting
confidence: 75%
“…We described related microbiome functional alterations and low MGR-related metabolomics signatures. We showed in severe obesity the presence of four enterotypes recently described in 40 individuals ranging from underweight to moderate obesity 25. Herein, very few severely obese patients harbour a Ruminococcaceae enterotype (ie, those who displayed the higher MGR).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We used DNA as the spike-in rather than whole cells because DNA quantitation is easier, more accurate and reproducible. Precise whole-cell count demands specialized equipment such as a flow cytometer [12], adds significant time and money to the endeavor, and is less reproducible. A whole-cell-based complex mock community of microbes was used to validate that the DNA extraction process lysed bacteria and fungi.…”
mentioning
confidence: 99%
“…Molecular analyses only would have limited comparisons to relative abundances, rather than enabling quantitative analyses (Vandeputte et al 2017;Geisen et al 2018). However, we acknowledge that the community composition that we provide might not represent abundances as provided by morphological identifications (Darby, Todd & Herman 2013).…”
Section: Discussionmentioning
confidence: 99%